2021
DOI: 10.3233/cbm-200643
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preoperative systemic immune-inflammation index in combined hepatocellular-cholangiocarcinoma

Abstract: BACKGROUND: Inflammation-based prognostic scores have been increasingly used for prognosis prediction in malignant tumors. However, no existing study has comprehensively evaluated these scores in combined hepatocellular-cholangiocarcinoma (cHCC-CCA). OBJECTIVE: This study aimed to identify a robust inflammation-based prognostic predictor for cHCC-CCA. METHODS: We retrospectively analyzed 220 patients pathologically confirmed as Allen type C cHCC-CCA. The univariate and multivariate analyses were used to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…After screening titles and abstracts, 18 studies were excluded. Finally, 10 studies comprising 2,508 patients were included in the meta-analysis [15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening titles and abstracts, 18 studies were excluded. Finally, 10 studies comprising 2,508 patients were included in the meta-analysis [15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…All 10 identified studies were retrospective cohorts, and the number of patients in each study ranged from 28 to 691. The included studies were published between 1993 and 2021 and were conducted in seven countries, including one multiinstitution (USA, Italy, Australia, China, France, the Netherlands, and Japan) [16], one in Japan [17], and eight in China [14,[18][19][20][21][22][23][24]. All studies provided information on the relationship between the SII and OS [15][16][17][18][19][20][21][22][23][24], three on RFS [22][23][24] and seven on clinicopathological features [17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic inflammation is vital in tumor development and progress in several cancers (6), including CCA (7). Previous studies have demonstrated that serum systemic inflammatory markers, including neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), and can help predict the survival of CCA patients (8)(9)(10). In addition, nutritional status is also helpful for predicting the prognosis of CCA (11).…”
Section: Introductionmentioning
confidence: 99%
“… 10 Currently, accumulating evidence has shown that inflammation‐based scores, such as systemic immune‐inflammation index (SII), platelet‐to‐lymphocyte ratio (PLR), neutrophil‐to‐lymphocyte ratio (NLR), lymphocyte‐to‐monocyte ratio (LMR), prognostic nutritional index (PNI), aspartate aminotransferase/platelet count ratio index (APRI), aspartate aminotransferase (AST) to neutrophil ratio index (ANRI), and AST to lymphocyte ratio index (ALRI) could be used as the prognostic markers for cholangiocarcinoma. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 Gamma‐glutamyl transpeptidase (GGT) to albumin ratio (GAR) was a newly identified inflammation‐based score. Initially, GAR was pointed out to be useful for stratification of patients with chronic hepatitis B.…”
Section: Introductionmentioning
confidence: 99%